Peppermint extract-compound nanofiber production and characterization - Sünter Eroğlu, Nilşen; Canoğlu, Suat (International journal of clothing science and technology, 2025)
PurposeAs a result of referee evaluation, the subject scope of the article has been expanded. Previously, only polycaprolactone (PCL) loaded with peppermint extract had been studied. As a result of peer review, nanostructure production was made with peppermint-loaded polylactic acid (PLA). Literature information about PLA polymer has been added to the Introduction section. Additionally, to analyze the presence of peppermint extract in Fourier transform infrared (FTIR) measurements, a comparison was made with 100% PCL, 100% PLA and 100% peppermint extract. In order to observe the effect of polymer type, evaluations were made between the produced peppermint-loaded nanostructures containing two different polymers. Mechanical, structural and morphological properties of the produced nanostructures were measured. The main purpose of the study is to analyze and evaluate peppermint-loaded nanostructures on different polymers.Design/methodology/approachNanofiber structures were produced by the electrospinning process due to their attractive properties such as low cost, flexibility, integrability and high efficiency. The production parameters of the nanofiber structure produced by the electrospinning process, mechanical measurements, fiber morphologies with scanning electron microscope (SEM) and structural characterization with FTIR measurement were analyzed, and its potential in possible usage areas was interpreted.FindingsIn this study, the production of nanostructures containing peppermint extract with PCL and PLA polymers, which are various biodegradable and biocompatible polymeric materials, was successfully achieved. In the studies carried out, nanofiber structures with positive properties such as low cost, easy accessibility, flexibility, integrability and sustainability were produced. When the two nanofiber structures produced were compared, it was observed that the peppermint extract nanofiber structure containing PCL provided better morphological and mechanical properties, such as higher strength, thinner fibers' diameter and a smooth and homogeneous surface, compared to the peppermint core nanofiber structure containing PLA. It has been observed that PCL polymer is more advantageous in obtaining nanofibers under the same environmental conditions and the same parameters. The addition of peppermint extract caused an approximately 25% loss in strength in nanostructures containing PCL polymer compared to nanostructures containing 100% PCL. The strength loss in PLA nanostructures containing peppermint extract is approximately 90% compared to nanostructures containing 100% PLA. This situation is associated with the regular arrangement of nanostructures containing PCL. In conclusion, incorporating peppermint extract into the nanofiber structures fabrication process offers several benefits, including enhanced antimicrobial properties and potential bioactive effects.Originality/valueIn the study, a uniform and suitable-for-use nanofiber structure with a smooth and partially beaded surface was obtained by an electrospinning method using peppermint extract and PCL and PLA polymers. Morphological evaluation was made with SEM images of the obtained nanofiber structure, and the presence of peppermint extract in the nanofiber structure was determined by the FTIR analysis. In the mechanical analysis, a decrease was observed in the elongation at break and tensile strength values of nanostructures loaded with mint extract, but this decrease did not prevent the production and use of the nanofiber structure.